2008
DOI: 10.1126/science.1163086
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Rac by the GAP Activity of Centralspindlin Is Essential for Cytokinesis

Abstract: During cytokinesis, the small GTPase RhoA orchestrates contractile ring assembly and constriction. RhoA signaling is controlled by the central spindle—a set of microtubule bundles that forms between the separating chromosomes. Centralspindlin, a protein complex consisting of the kinesin-6 ZEN-4, and the Rho GAP CYK-4, is required for central spindle assembly and cytokinesis. However, the importance of the CYK-4 GAP activity and whether it regulates RhoA remains unclear. Here, we show that two separation-of-fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
232
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(249 citation statements)
references
References 29 publications
16
232
0
1
Order By: Relevance
“…Both subunits are vital for microtubule bundling in vitro and central spindle formation in vivo. The atomic structure of centralspindlin is not known, except for the GAP domain of CYK4, whose target Rho-family GTPase is under debate (Canman et al, 2008;JantschPlunger et al, 2000;Miller and Bement, 2009;Yamada et al, 2006;Zavortink et al, 2005). Similar to PRC1, the interaction of centralspindlin with microtubules is suppressed by CDK1 phosphorylation before anaphase onset (Goshima and Vale, 2005;Mishima et al, 2004).…”
Section: Centralspindlinmentioning
confidence: 99%
“…Both subunits are vital for microtubule bundling in vitro and central spindle formation in vivo. The atomic structure of centralspindlin is not known, except for the GAP domain of CYK4, whose target Rho-family GTPase is under debate (Canman et al, 2008;JantschPlunger et al, 2000;Miller and Bement, 2009;Yamada et al, 2006;Zavortink et al, 2005). Similar to PRC1, the interaction of centralspindlin with microtubules is suppressed by CDK1 phosphorylation before anaphase onset (Goshima and Vale, 2005;Mishima et al, 2004).…”
Section: Centralspindlinmentioning
confidence: 99%
“…Initial evidence indicated that this GAP is significantly more active in vitro toward Rac, another member of the Rho family of GTPases, rather than RhoA (Toure et al 1998;JantschPlunger et al 2000). Subsequently, genetic studies in Drosophila and C. elegans also suggested that RacGAP1 could inactivate Rac GTPases in vivo (D'Avino et al 2004;Canman et al 2008), and this would inhibit the formation of a branched actomyosin web and, therefore, reduce stiffness at the equatorial cortex ( Fig. 3) (D'Avino et al 2005;Canman et al 2008).…”
Section: Cleavage Furrow Ingression: Actomyosin Filaments Take Centermentioning
confidence: 99%
“…Subsequently, genetic studies in Drosophila and C. elegans also suggested that RacGAP1 could inactivate Rac GTPases in vivo (D'Avino et al 2004;Canman et al 2008), and this would inhibit the formation of a branched actomyosin web and, therefore, reduce stiffness at the equatorial cortex ( Fig. 3) (D'Avino et al 2005;Canman et al 2008). Evidence in human cells also indicated that the GAP activity of RacGAP1 could be required to inhibit Rac-dependent pathways involved in cell adhesion and spreading ( Fig.…”
Section: Cleavage Furrow Ingression: Actomyosin Filaments Take Centermentioning
confidence: 99%
“…In contrast to RHO‐1/RhoA's role, CED‐10/Rac might be a negative regulator of cytokinesis 24. In C. elegans it has been shown that CED‐10/Rac repression by the GAP activity of CYK‐4 is necessary for downregulating Rac GTPases at the cleavage site in order to drive cytokinesis.…”
Section: Rac/rho Small Gtpases Mediate Spindle Orientation and Cell Dmentioning
confidence: 99%
“…Inhibition of CED‐10/Rac at the division plane is essential in order to prevent Arp2/3 complex activation, (which induces branched actin polymerization), thus reducing cell adhesions and permitting contractile ring constriction. This inactivation of CED‐10/Rac by Centralspindlin functions in parallel with RHO‐1/RhoA activation in the same location to drive cytokinesis 24. However, the function of the CYK‐4 RhoGAP domain seems to depend on the biological system and the CYK‐4 mutations used in the experiments 25.…”
Section: Rac/rho Small Gtpases Mediate Spindle Orientation and Cell Dmentioning
confidence: 99%